Does coordination asymmetry relate to unilateral breathing and/or impairment side in front crawl paralympic swimmers? - Seifert, L.; Létocart, A.; Guignard, B.; Regaieg, M. A. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
The aim of our study was to investigate whether coordination asymmetry relates to unilateral breathing and/or impairment side in paralympic swimmers. We hypothesized that paraswimmers exhibited arm coordination asymmetry. We also hypothesized that arm coordination asymmetry further occurred on the impaired side and on the preferential breathing side. The second aim examined the effect of swimming speed on arm coordination asymmetry. We hypothesized that arm coordination asymmetry mainly occurred at high speeds as unilateral breathing might further unbalance propulsion organization.